DETERMINE OF STOCK PRICE VOLATILITY ON MINING COMPANIES ON THE INDONESIA STOCK EXCHANGE - Nurhasanah Nurhasanah; Husaini Husaini; Arliansyah Arliansyah; Johanda Syahputra (RADJA PUBLIKA, 2022)
The purpose of this study was to determine the effect of dividend policy, earning volatility, trading volume, exchange rates and interest rates on the volatility of stock prices in mining companies on the Indonesia Stock Exchange. The population studied in this study were all mining companies which were mining companies for the 2016-2019 period totaling 51. The sampling technique inthis study used a positive sampling method. The samples in this study were as many as 14 mining companies with the 2016-2019 observation year. The data analysis method used in this study is thepanel data regression analysis method. Dividend policy has a positive but insignificant effect on stock price volatility in mining companies on the Indonesia Stock Exchange. Profit volatility has a positive but insignificant effect on the volatility of share prices in mining companies on the Indonesia Stock Exchange. Trading volume has a positive and significant effect on the volatility of share prices in mining companies on the Indonesia Stock Exchange. Exchange rates have a positive and significant effect on stock price volatility in mining companies on the Indonesia Stock Exchange. Interest rates have a positive and significant effect on the volatility of share prices in mining companies on the Indonesia Stock Exchange.